2021
DOI: 10.1021/acscentsci.1c00070
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Antagonist Modulation of TRPV2 by Piperlongumine Impairs Glioblastoma Progression

Abstract: The use of computational tools to identify biological targets of natural products with anticancer properties and unknown modes of action is gaining momentum. We employed self-organizing maps to deconvolute the phenotypic effects of piperlongumine (PL) and establish a link to modulation of the human transient receptor potential vanilloid 2 (hTRPV2) channel. The structure of the PL-bound full-length rat TRPV2 channel was determined by cryo-EM. PL binds to a transient allosteric pocket responsible for a new mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…Of other inhibitory binding sites in TRP channels, the location of the econazole-binding site in TRPV6 (Fig. 4 ) has the highest similarity with the location of a piperlongumine-binding site in TRPV2 65 . Compared with the econazole-binding site in TRPV6, the piperlongumine-binding site in TRPV2 is wedged deeper between S4 and S5 and makes contact with S6.…”
Section: Discussionmentioning
confidence: 99%
“…Of other inhibitory binding sites in TRP channels, the location of the econazole-binding site in TRPV6 (Fig. 4 ) has the highest similarity with the location of a piperlongumine-binding site in TRPV2 65 . Compared with the econazole-binding site in TRPV6, the piperlongumine-binding site in TRPV2 is wedged deeper between S4 and S5 and makes contact with S6.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is yet unclear how clinical therapeutics can be altered to target this intra and intertumoral heterogeneity. We must consider therapies that address multiple resistance pathways, including immune-based therapies that may target multiple tumor antigens (19,(161)(162)(163), or therapies targeting common metabolic and physiological pathways, which may improve chances of success (164,165). Furthermore, greater effort in developing preclinical models and clinical studies to understand spatial heterogeneity, tumor recurrence, and evolutionary trajectories in GBM are vital (Figure 2).…”
Section: Glioma Heterogeneity and Tme In Clinical Therapeutic Resistancementioning
confidence: 99%
“…Residues forming the ion pore are indicated. Lower right inset , Piperlongumine binding site of TRPV2 (PDB 6WKN [ 53 ]), with TRPV2 cartoon colored by subunit and piperlongumine in stick representation. Key interacting residues are shown as sticks.…”
Section: Gpcrsmentioning
confidence: 99%
“…Electrophysiological studies revealed the channel to be active in the presence of CBD when reconstituted in liposomes, but to open occasionally for extended periods even in the apo form, suggesting membrane lipids may modulate its activity. A follow-up structure of TRPV2 was reported this year in the presence of piperlongumine, a naturally occurring alkaloid with selective anti-cancer properties [ 53 ]. Notably, the activity of piperlongumine was predicted computationally using SPIDER, a tool used to identify associations between small molecules and their protein targets, and it was subsequently validated in vivo as a TRPV2 antagonist.…”
Section: Ion Channelsmentioning
confidence: 99%